Supervisi Pendidikan Yang Inklusif Dalam Menyikapi Keberagaman Di Madrasah Tsanawiyyah - Ma’shum Thoyib; Sabarun Jamil (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This research aims to optimize inclusive education supervision in addressing diversity in the classroom. The object of this research concerns inclusive educational supervision in addressing diversity in classes located in class 9 c of Madrasah Tsanawiyyah Al-Amiriyyah, Blokagung, Banyuwangi, East Java. This research method uses qualitative with a case study approach. Sources of informants in this research include; Principal, Teachers, Students. Data collection techniques used in this research include observation, document analysis, and interviews. Data analysis in this research uses the Miles and Huberman data analysis model, which consists of three main components: data reduction, data analysis, and data conclusions. The results of research on inclusive educational supervision in addressing diversity in the classroom include; Differentiated Approach in Supervision, Parental Involvement, Emotional Impact on Students.